Ministry Of Finance Decree No. 416 Of The Year 2010 On The Amendment Of Some Provisions Of The Executive Regulations Implementing Law On Organizing Customs Exemptions Promulgated By The Decree Of Minister Of Finance No. 861 Of The Year 2005 = وزارة المالية قرار رقم 416 لسنة 2010 بتعديل بعض أحكام اللائحة التنفيذية لقانون تنظيم الإعفاءات الجمركية الصادرة بقرار وزير المالية رقم 861 لسنة 2005 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.